Do behavioral nudges endure? Effect of reminders on sustained demand for quality seed of sweet potato - Okello, J.J.; Just, D.; Verschoor, A.; Xie, M.; Mulwa, C.K.; Ojwang, S.O.; Mwende, J.; Namanda, S.; Ssali, R.T.; Yada, B.; Rajendran, S.; Campos, Hugo (2024)
Delivering quality seed of to farmers is critical to the development of smallholder crop sector in developing countries. Smallholder farmers continue to use poor quality recycled seed obtained from own or social network. Behavioral nudges are currently being considered as a low-cost approach of stimulating demand for agricultural innovations including quality seed. However, past studies continue to cast doubt on the longevity of nudges. That is, there is doubt on whether nudges can be used to stimulate sustained demand for agricultural innovations. In this study, we examine whether nudges may be used to influence sustained adoption of quality seed of improved sweetpotato varieties (QS-ISV) in an informal seed system. The seed used in the study were inspected and certified as disease and pest-free. We focus on the use of text message reminders designed to increase the repurchase of QS-ISV introduced into informal farmer network-based seed systems. The study site is a sweetpotato growing district in Uganda where yield is severely depressed due to sweetpotato virus diseases and pests, especially sweetpotato weevils. The study used a randomized controlled trial in which quality seed was displayed for sale in all study villages with treatment group receiving text message reminders, while the control group only getting exposure to QS-ISV. Seed was presented at salespoints for three consecutive seasons with reminders being sent for two consecutive seasons focusing on seed purchasers in the first two seasons. We find that reminders initially increased the likelihood of seed repurchase and subsequently, when reminders are repeated, reduce this likelihood. This suggests that nudges may be used to encourage the swifter integration of formal and informal elements in seed systems, but that their overuse may be counterproductive.